Effect of pH-sensitive nanoparticles on inhibiting oral biofilms - Xinyu Peng; Qi Han; Xuedong Zhou; Yanyan Chen; Xiaoyu Huang; Xiao Guo; Ruiting Peng; Haohao Wang; Xian Peng; Lei Cheng (Taylor & Francis Group, 2022)
Dental caries is a biofilm-related preventable infectious disease caused by interactions between the oral bacteria and the host's dietary sugars. As the microenvironments in cariogenic biofilms are often acidic, pH-sensitive drug delivery systems have become innovative materials for dental caries prevention in recent years. In the present study, poly(DMAEMA-co-HEMA) was used as a pH-sensitive carrier to synthesize a chlorhexidine (CHX)-loaded nanomaterial (p(DH)@CHX). In vitro, p(DH)@CHX exhibited good pH sensitivity and a sustained and high CHX release rate in the acidic environment. It also exhibited lower cytotoxicity against human oral keratinocytes (HOKs) compared to free CHX. Besides, compared with free CHX, p(DH)@CHX showed the same antibacterial effects on S. mutans biofilms. In addition, it had no effect on eradicating healthy saliva-derived biofilm, while free CHX exhibited an inhibitory effect. Furthermore, the 16s rDNA sequencing results showed that p(DH)@CHX had the potential to alter oral microbiota composition and possibly reduce caries risk. In conclusion, the present study presents an alternative option to design an intelligent material to prevent and treat dental caries.